2011
DOI: 10.11646/zootaxa.3083.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of the Neotropical poison frog genus Ranitomeya (Amphibia: Dendrobatidae)

Abstract: The Neotropical poison frog genus Ranitomeya is revised, resulting in one new genus, one new species, five synonymies and one species classified as nomen dubium. We present an expanded molecular phylogeny that contains 235 terminals, 104 of which are new to this study. Notable additions to this phylogeny include seven of the 12 species in the minuta group, 15 Ranitomeya amazonica, 20 R. lamasi, two R. sirensis, 30 R. ventrimaculata and seven R. uakarii. Previous researchers have long recognized two distinct, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 0 publications
2
98
1
14
Order By: Relevance
“…The greatest intraspecific distances were recorded in Ranitomeya ventrimaculata (12.9%), Leptodactylus knudseni , Hypsiboas leptolineatus (13.3%), and Scinax fuscomarginatus (10.9%). A similar degree of divergence was found in Ranitomeya ventrimaculata by Symula et al (2003) and Brown et al (2011). Likewise, Kok and Kalamandeen (2008) have suggested that Leptodactylus knudseni may represent a species complex.…”
Section: Discussionsupporting
confidence: 54%
“…The greatest intraspecific distances were recorded in Ranitomeya ventrimaculata (12.9%), Leptodactylus knudseni , Hypsiboas leptolineatus (13.3%), and Scinax fuscomarginatus (10.9%). A similar degree of divergence was found in Ranitomeya ventrimaculata by Symula et al (2003) and Brown et al (2011). Likewise, Kok and Kalamandeen (2008) have suggested that Leptodactylus knudseni may represent a species complex.…”
Section: Discussionsupporting
confidence: 54%
“…They appear to coincide with a change in the local model species community; for example, the transition zone from the banded to striped morphs occurring near Callanayacu appears to coincide with the distribution of the two local model species ( R. summersi, present southwest of Callanayacu, and striped R. variabilis , present northeast). In the transition zone between the striped and spotted morphs occurring in the foothills south of Pongo de Cainarachi, the color pattern of R. imitator closely tracks intraspecific variation in a single, polymorphic model species, R. variabilis (previously considered to be two species [34]), which varies along an elevation gradient.…”
Section: Resultsmentioning
confidence: 66%
“…Chouteau et al [26] raised concerns about the usage of these terms based on genetic differentiation between two close populations of co-mimetic R. imitator and R. variabilis. However, phylogeographic evidence provides additional support for the advergence hypothesis, with R. imitator mimicking two other (distantly related) species in other localities [12,22-24]. There is also evidence for recent divergence under selection in R. imitator [24], and evidence for multiple independent lineages of a highland spotted morph of R. variabilis , even in areas well outside the range of R. imitator [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, phylogeographic evidence provides additional support for the advergence hypothesis, with R. imitator mimicking two other (distantly related) species in other localities [12,22-24]. There is also evidence for recent divergence under selection in R. imitator [24], and evidence for multiple independent lineages of a highland spotted morph of R. variabilis , even in areas well outside the range of R. imitator [12]. Although we typically refer to these species as “co-mimics” throughout the paper, when relevant we use the term ‘mimic’ to refer to R. imitator and ‘model’ to refer to co-mimetic congeners ( R. fantastica, R. summersi, and R. variabilis ).…”
Section: Introductionmentioning
confidence: 99%